Evaluate the Effectiveness of the Inventory Accounting Information System in Supporting Internal Control - Sina Delphia Sukmana; Henryanto Wijaya (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study aims to evaluate the effectiveness of the inventory accounting information system in supporting internal controls at PT Harapan Indah, which still uses manual and semi-computerized systems. Research Method: This study employed a qualitative descriptive case study design. Data were collected through interviews, observations, and documentation from five informants, including members of the accounting and financial management departments and warehouse staff. Data analysis was conducted through data reduction, thematic coding, data presentation, and the drawing of conclusions using the COSO Internal Control Integrated Framework and the Information System Success Model. Results and Discussion: The research findings indicate that the inventory accounting information system has supported the company’s operational activities; however, its effectiveness in supporting internal controls remains moderate. Key weaknesses include a lack of system integration, access restrictions, audit trails, and documented risk assessment procedures. Implications: This study underscores the importance of integrating digital systems and strengthening risk-based internal controls. Originality: The novelty of this research lies in integrating the COSO framework and the Information System Success Model in the context of semi-computerized systems.